Some Relations of the Twisted q-Genocchi Numbers and Polynomials with Weight α and Weak Weight β - J. Y. Kang; H. Y. Lee; N. S. Jung (Abstract and Applied Analysis)
Recently many mathematicians are working on Genocchi polynomials and Genocchi numbers. We define a new type of twisted q-Genocchi numbers and polynomials with weight 𝛼 and weak weight 𝛽 and give some interesting relations of the twisted q-Genocchi numbers and polynomials with weight 𝛼 and weak weight 𝛽. Finally, we find relations between twisted q-Genocchi zeta function and twisted Hurwitz q-Genocchi zeta function.